Some aspects of the nutrition of West Malaysian primates in the wild - Vellayan, S. (Veterinary Association Malaysia, 1982)
The diets of the thirteen species of' the West Malaysian primates are discussed, Food items of the nine higher primates can be classified into four categories namely, fruits, leaves, flowers, insects and water. Based on the above classification, the Hylobates syndactylus is floigivar us; Hylobates lar and Hylobates agilis are frugivorous; Macaca fascicularis, M. nemestrina and M. arctoides are omnivorous: Presbytis obscura and P. cristata are foligivarous while P. melalophos.is frugivorous. The mode end source of water intake is more of else the same in all the species.